Is South Africa Failing to Uphold its Human Rights Obligation with Respect to Right to Basic Education Through Extermination of Pit Latrines in Schools? Implications for Department of Basic Education - Banda Chitsamatanga, Bellita; Ntlama-Makhanya., Nomthandazo (Alberta Journal of Educational Research, 2022)
The right to basic education of a child is a requirement of human dignity. South Africa, through its new dispensation and conformity with human rights laws, is expected to transform and be consistent with the provision of the Constitution of 1996 that promotes and protects the best interest of the child. However, the current standards in a majority of South African schools, particularly in impoverished provinces, has clearly demonstrated the urgent need for rapid fundamental changes. This article provides a review of the constitutional right to basic education with reference to the welfare of the learners in South African schools and raises questions as to whether South Africa is out-of-depth in upholding its constitutional obligation with respect to the right to basic education in the eradication of pit latrines in schools. It argues that the lack of adequate resources in the provisioning of sanitation undermines many of the fundamental rights that are entrenched in the Constitution 1996. An overview of the international conventions and human rights treaties to which South Africa is a signatory is given, showing the country’s commitment to protecting and improving the status and welfare of the children. Furthermore, the second section intersects the right to basic education with the best interest of the child as envisaged in South Africa’s legal framework. The final section details how despite legislation in place, the existence of pit latrines in schools violates the right to life, health, and dignity of its learners, particularly the right to basic education. Key words: children, education, human rights and dignity, pit latrines, schools Le droit de l’enfant à l'éducation de base est une exigence de la dignité humaine. L'Afrique du Sud, à travers sa nouvelle dispensation et sa conformité avec les lois sur les droits de l'homme, est censée se transformer et être cohérente avec la disposition de la Constitution de 1996 qui promeut et protège l'intérêt supérieur de l'enfant. Cependant, les normes actuelles dans une majorité d'écoles sud-africaines, en particulier dans les provinces pauvres, ont clairement démontré le besoin urgent de changements fondamentaux rapides. Cet article passe en revue le droit constitutionnel à l'éducation de base en se référant au bien-être des apprenants dans les écoles sud-africaines et soulève la question de savoir si l'Afrique du Sud perd pied quant à son obligation constitutionnelle en ce qui concerne le droit à l'éducation de base dans l'éradication des latrines à fosse dans les écoles. Il affirme que le manque de ressources adéquates pour la fourniture de services d'assainissement porte atteinte à de nombreux droits fondamentaux inscrits dans la Constitution de 1996. On présente un aperçu des conventions internationales et des traités relatifs aux droits de l'homme dont l'Afrique du Sud est signataire, montrant l'engagement du pays à protéger et à améliorer le statut et le bien-être des enfants. En outre, la deuxième section met en relation le droit à l'éducation de base avec l'intérêt supérieur de l'enfant tel qu'il est envisagé dans le cadre juridique sud-africain. La dernière section détaille comment, malgré la législation en place, l'existence de latrines à fosse dans les écoles viole le droit à la vie, à la santé et à la dignité de ses apprenants, en particulier le droit à l'éducation de base. Mots clés: enfants, éducation, droits de l'homme et dignité, latrines à fosse, écoles